Critical Analysis of Key Healthcare Challenges in The Modern Era - Al Harshan, Nasser Hadi Ali; Al-Theban, Saleh Hamad Hassan; Alsowidah, Layla Nasser Mohammad; Alrabie, Hamad Owaydhah Saleh; Al Haider, Shaya Abdullah Abdullah; Buayti, Yasir Qasem Mahdi; Haqawi, Ali Mohammed Hamoud; Al Mansour, Mohammed Ali Mohammed; Al Yami, Mohammed Hadi Mari’ Al Shaiban; Alhassan, Abdullah Hejji Ahmed (Journal of Ecohumanism, 2024)
Modern healthcare systems endeavor to be world-class, delivering treatment and care to individuals across the globe. In so doing, they are faced with an obligatory of challenges which are formal due to various global threats, demographic changes, technologies, and constraints of the economies in the contemporary world. This paper assesses the following major issues: the issue of access to health care, the increasing concern of health care costs, the maldistribution of health care workforce, health disparities/inequities, and the role of technology in healthcare systems. After reviewing numerous papers, performing data analysis, and incorporating interpretive explanations, this research reveals the preceding challenges and their effects on healthcare delivery and offers implied solutions. Using figures, tables, and graphs, this paper comprehensively analyzes the various key challenges facing the modern-day healthcare system.